Early diagnosis and the effect of treatment compliance on the prognosis and progression of glaucomatous optic neuropathy - S.V. Diordiychuk; A.V. Kuroyedov; N.E. Fomin; O.V. Gapon’ko; V.V. Gorodnichiy; I.V. Kondrakova; N.M. Sol’nov (РМЖ "Клиническая офтальмология")
S.V. Diordiychuk1, A.V. Kuroyedov1,2, N.E. Fomin1,2, O.V. Gapon’ko1,2, V.V. Gorodnichiy1, I.V. Kondrakova1, N.M. Sol’nov1 1P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation This paper addresses the results of long-term monitoring of primary open-angle glaucoma. The specificity of this case report is a long-term observation period at one hospital and the use of standardized diagnostic tools. Moreover, dynamic monitoring was performed using the same devices to assess structural and functional alterations of the retina and optic nerve. This practice minimizes measurement errors when evaluating the structural and functional alterations of the retina and optic nerve. The described disease course has demonstrated that several factors affect the prognosis and development of a chronic progressive neurodegenerative disorder, which results in irreversible blindness. These factors include early diagnosis, accessible and effective screening system, rational management strategy that implies the drug change to prevent the reduction in therapeutic effect, and patient adherence to treatment that involves explaining the causes and characteristics of disease cours e, potential complications with recommendation noncompliance, and a professional work a doctor with a patient. Keywords: primary open-angle glaucoma, glaucomatous optic neuropathy (GON), compliance, diagnosis, monitoring, vision. For citation: Diordiychuk S.V., Kuroyedov A.V., Fomin N.E. et al. Early diagnosis and the effect of treatment compliance on the prognosis and progression of glaucomatous optic neuropathy. Russian Journal of Clinical Ophthalmology. 2021;21(1):34–39. DOI: 10.32364/2311-7729-2021-21-1-34-39.